2020
DOI: 10.2147/pgpm.s269726
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identifying the Mechanisms and Molecular Targets of Yizhiqingxin Formula on Alzheimer’s Disease: Coupling Network Pharmacology with GEO Database</p>

Abstract: Background: Yizhiqingxin formula (YZQX) is a promising formula for the treatment of Alzheimer's disease (AD) with significant clinical effects. Here, we coupled a network pharmacology approach with the Gene Expression Omnibus (GEO) database to illustrate comprehensive mechanisms and screen for molecular targets of YZQX for AD treatment. Methods: First, active ingredients of YZQX were screened for the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database with the absorption, distribution, metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…This paper is purposed to predict the targets and underlying mechanism of Celastrol in reversing the early energy remodeling for DCM. So, network pharmacology concepts and methodologies were applied in this study to explore the key targets of Celastrol against DCM, as well as the pathways involved in the mechanism of action of DCM [ 17 19 ]. According to the relevant principles and methods of network pharmacology [ 17 , 20 ], we not only analyzed the main targets of Celastrol on DCM but also applied the research methods of “Li et al” to predict and analyze its enriched biological processes and signaling pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper is purposed to predict the targets and underlying mechanism of Celastrol in reversing the early energy remodeling for DCM. So, network pharmacology concepts and methodologies were applied in this study to explore the key targets of Celastrol against DCM, as well as the pathways involved in the mechanism of action of DCM [ 17 19 ]. According to the relevant principles and methods of network pharmacology [ 17 , 20 ], we not only analyzed the main targets of Celastrol on DCM but also applied the research methods of “Li et al” to predict and analyze its enriched biological processes and signaling pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[44] Multiple AD-related network pharmacology literature reported that AKT1 plays a crucial role in AD. [43][44][45][46][47] IL6, TNF, and IL1B are often used as proinflammatory markers in AD. [48,49] The remaining core targets are all playing essential roles in AD.…”
Section: Discussionmentioning
confidence: 99%
“…This network-based approach can explain the combination rules and network regulation effects of herbal formulas [ 21 ]. Network pharmacology strategies were successfully used to reveal mechanism of Lang Chuang Wan in treating systemic lupus erythematosus [ 22 ] and Yizhiqingxin formula on Alzheimer’s disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%